Diversity of Lysis-Resistant Bacteria and Archaea in the Polyextreme Environment of Salar de Huasco - Corona Ramírez, Andrea; Cailleau, Guillaume; Fatton, Mathilda; Dorador, Cristina; Junier, Pilar (Frontiers in Microbiology, 2022)
The production of specialized resting cells is a remarkable strategy developed by several organisms to survive unfavorable environmental conditions. Spores are specialized resting cells that are characterized by a low to absent metabolic activity and by a higher resistance. Spore-like cells are known from multiple groups of bacteria, which are able to form spores under suboptimal growth conditions (e.g. starvation). In contrast, little is known about the production of specialized resting cells in archaea. In this study we applied a culture-independent method that uses physical and chemical lysis, to assess the diversity of lysis-resistant bacteria and archaea and compare it to the overall prokaryotic diversity (direct DNA extraction). The diversity of lysis-resistant cells was studied in the polyextreme environment of the Salar de Huasco. The Salar de Huasco is a high-altitude athalassohaline wetland in the Chilean Altiplano. Previous studies have shown a high diversity of bacteria and archaea in the Salar de Huasco, but the diversity of lysis-resistant microorganisms has never been investigated. The underlying hypothesis was that the combination of extreme abiotic conditions might favor the production of specialized resting cells. Samples were collected from sediment cores along a saline gradient and from microbial mats collected in small surrounding ponds. A significantly different diversity and composition were found in the sediment cores or microbial mats. Furthermore, our results show a high diversity of lysis-resistant cells not only in bacteria but also in archaea. The bacterial lysis-resistant fraction was distinct in comparison to the overall community. Also, the ability to survive the lysis-resistant treatment was restricted to a few groups, including known spore-forming phyla such as Firmicutes and Actinobacteria. In contrast to bacteria, lysis-resistance was widely spread in archaea, hinting to a generalized resistance to lysis, which is at least comparable to the resistance of dormant cells in bacteria. The enrichment of Natrinema and Halarchaeum in the lysis-resistant fraction could hint to the production of cyst-like cells or other resistant cells. These results can guide future studies aiming to isolate and broaden the characterization of lysis-resistant archaea.